Development of a conceptual model to improve the quality of product portfolio - A. A. Demyanov (Путеводитель предпринимателя, 2020)
In this article, the author develops a conceptual model to improve the quality of product portfolio of a business entity. This model includes a number of products produced by the company, who have a mutual influence on each other. This leads to a positive effect on the quality ofeach product. Mutual influence can be carried out oforganizational measures, as well as economic. Under the institutional arrangements means any action aimed at achieving this goal (improving quality) based on organizational methods that do not require financial costs or those costs are negligible. Economic activities include actions aimed at improving the quality of using the methods of the economic plan, based on which to contain costs.